2015
DOI: 10.1007/s10517-015-2828-6
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Apoptosis Regulation in Hepatocytes Induced by First-Line Antitubercular Drugs

Abstract: We studied pathways of apoptosis regulation during experimental hepatopathy caused by treatment with antitubercular drugs and involvement of some hepatoprotectors and immunomodulators in the regulation of hepatocyte apoptosis induced by antitubercular drugs. The intensity of apoptosis and expression of apoptosis-associated molecules were evaluated. It was shown that antitubercular drugs induce apoptosis in hepatocytes by triggering external signaling pathway and p53-dependent signaling pathway and simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Inhibition of P53 and its nuclear translocation by IL-17 impairs apoptosis of the Mtb-infected cells via reduction of caspase-3, Bax, and cytochrome-c release, as well as by increasing Bcl2 [ 170 ]. The ethanolic extract of Pluchea indica and other antitubercular drugs exhibited anti-tuberculosis and anti-inflammatory effects by P53-mediated apoptosis [ 171 , 172 ].…”
Section: Copdmentioning
confidence: 99%
“…Inhibition of P53 and its nuclear translocation by IL-17 impairs apoptosis of the Mtb-infected cells via reduction of caspase-3, Bax, and cytochrome-c release, as well as by increasing Bcl2 [ 170 ]. The ethanolic extract of Pluchea indica and other antitubercular drugs exhibited anti-tuberculosis and anti-inflammatory effects by P53-mediated apoptosis [ 171 , 172 ].…”
Section: Copdmentioning
confidence: 99%
“…The mechanism of ATD-induced DILI involves both the external apoptosis pathway mediated by the cell surface receptor Fas and the internal apoptotic pathway, which is p53-dependent. Simultaneously, the level of antiapoptotic Bcl-2 protein was reduced 141. Decreased intracellular antioxidases (eg, superoxide dismutase) and elevated ROS generation also play a role 139…”
Section: Hepatocyte Apoptosis and Drug-induced Liver Injury (Dili)mentioning
confidence: 99%
“…140 Combined administration of isoniazid (50 mg/kg subcutaneously), rifampicin (250 mg/kg intragastrically), and pyrazinamide (45 mg/kg intragastrically) for 14 days in rats significantly induced hepatocyte apoptosis. 141 The mechanism of ATD-induced DILI involves both the external apoptosis pathway mediated by the cell surface receptor Fas and the internal apoptotic pathway, which is p53-dependent. Simultaneously, the level of antiapoptotic Bcl-2 protein was reduced.…”
Section: Hepatocyte Apoptosis and Drug-induced Liver Injury (Dili)mentioning
confidence: 99%
See 1 more Smart Citation
“…Expression levels of important functional proteins are typically altered during cell apoptosis ( 33 35 ). The results of the present study, using 2D analysis, revealed a significant decrease of 14-3-3ε in the nuclear matrix of apoptotic MG-63 cells.…”
Section: Discussionmentioning
confidence: 99%